A COUP SPECTRUM ROUND AGAIN BRAZIL: THE RIGHTS TO BLOW - Irineu de Frana, Diego Pessoa [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2016)
This text aims at discussing the offense on the rights of us, in the last years, in Brazil, which has to do with the neoliberal reduction of the achievements made by the working class. This is the result of reflections I have been setting up, a little over a year ago, when the evidence of blow-orientated processes was intense. However, rather than intending to take this discussion with focus on merely circumstantial elements, I intend to identify the structure present in form of austerity enforced as unavoidable, as well as realizing what implications such measures may represent to the lives of Brazilians. For this purpose, the discussion over the Political Form of the State, as a crucial component for capital accumulation, becomes indispensable for us to understand the core of the processes underway, as it allows us to transcend the conjuncture immediateness and to realize the strengths and limitations of the progressive governments before the bourgeois State.
Keywords: blow to the rights; Political Form; State and government